2019
DOI: 10.1002/jmri.26768
|View full text |Cite
|
Sign up to set email alerts
|

Value of gadoxetic acid‐enhanced MRI and diffusion‐weighted imaging in the differentiation of hypervascular hyperplastic nodule from small (<3 cm) hypervascular hepatocellular carcinoma in patients with alcoholic liver cirrhosis: A retrospective case–control study

Abstract: Background: Hypervascular hyperplastic nodules (HHNs) occasionally develop in patients with alcoholic liver cirrhosis (ALC) and show arterial enhancement, thus mimicking hepatocellular carcinoma (HCC). Importantly, HHN as a benign lesion should be distinguished from HCC. Purpose: To evaluate the value of gadoxetic acid-enhanced MRI (Gd-EOB-MRI) and diffusion-weighted imaging (DWI) in distinguishing HHN from small (<3 cm) hypervascular HCC (hHCC) in patients with ALC. Study Type: Retrospective case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The findings of our study also demonstrated that HBP hypointensity seems to be a more sensitive imaging feature for the diagnosis of HCC with the sensitivity of 97.14% (170/175); however, in our study, 5 HCCs (2.86%; 5/175) with well-differentiated characteristics presented hyperintensity on HBP and which lead to the false negative identification. In addition, it comes to our attention that the imaging feature of DWI hyperintensity entails a high diagnostic sensitivity of 96.00% (168/175) and which is obviously higher than that of the previous studies reported from 75.9 to 87.6% [26, 28]. This difference can largely be attributed to 2 possible reasons: first, the inclusion criteria bias, as the previous studies mainly included small HCCs (<3 cm); thus, a high proportion of HCCs especially for those <1 cm would be neglected because of the thickness.…”
Section: Discussionmentioning
confidence: 77%
“…The findings of our study also demonstrated that HBP hypointensity seems to be a more sensitive imaging feature for the diagnosis of HCC with the sensitivity of 97.14% (170/175); however, in our study, 5 HCCs (2.86%; 5/175) with well-differentiated characteristics presented hyperintensity on HBP and which lead to the false negative identification. In addition, it comes to our attention that the imaging feature of DWI hyperintensity entails a high diagnostic sensitivity of 96.00% (168/175) and which is obviously higher than that of the previous studies reported from 75.9 to 87.6% [26, 28]. This difference can largely be attributed to 2 possible reasons: first, the inclusion criteria bias, as the previous studies mainly included small HCCs (<3 cm); thus, a high proportion of HCCs especially for those <1 cm would be neglected because of the thickness.…”
Section: Discussionmentioning
confidence: 77%
“…Mosaic architecture refers to the difference present within mass of randomly distributed internal nodules or compartments differing in enhancement, attenuation, intensity, shape, and size and often separated by fibrous separations [ 18 ]. It is characteristic of a heterogeneous signal on T2WI [ 19 ]; (b) Intralesional fat: the chemical shift of intralesional fat cause an area shows significantly lower signal intensity (SI) on opposed–phase imagesT1WI compared with the SI in-phase images [ 20 ], which confirmed the presence of steatosis [ 21 ]; (c) intratumor hemorrhage: with ahyper–SI on unenhanced T1WI and a hypo–SI on T2WI [ 21 ]; (d) Iso/Hyperintense SI (T1WI):isointense (hyper–isointense) SI in the lesion on T1WI; (e) T2–weighted and diffusion-weighted imaging (T2–DW) mismatch: T2–DW mismatch mainly means a morphological mismatch, with a larger mass on thediffusion weighted imaging (DWI) images than T2WI images. Because of the image distortion on the DWI images, it was not accurate that only compare the lesion diameter or area on DWI with T2WI.…”
Section: Methodsmentioning
confidence: 99%
“…The ADC values for metastases show a significant overlap between ADC values of benign hepatocellular lesions and other malignant lesions [14]. Lesion characterization should therefore be done considering also morphological and functional data obtained by T2-W and T1-W sequences and dynamic studies [15,16]. Various liver-specific contrast media (cm) have been developed to improve the detection and characterization of hepatic lesions.…”
Section: Introductionmentioning
confidence: 99%